Sergei Brukhonenko – the founder of cardiopulmonary bypass (philosophical, methodological and sociocultural context) - A. Y. Ivanyushkin; O. N. Reznik; O. V. Popova (Вестник трансплантологии и искусственных органов)
This paper is dedicated to Sergei Brukhonenko (1890–1960), a physiologist and inventor of the world’s first heartlung machine. His immense contributions to the development of modern science and technology are investigated. Brukhonenko’s invention is seen as modern biotechnology that has attracted an all-round strong public interest. A philosophical analysis of the differences between the concepts “technique” and “technology” is presented. The paper discusses the sociocultural impact of biotechnology on the society and culture.